2016
DOI: 10.1039/c6sc02106a
|View full text |Cite
|
Sign up to set email alerts
|

Zn⋯Zn interactions at nickel and palladium centers

Abstract: Zinc–zinc interactions on nickel and palladium centers are highly dependent on the co-ligands. These dependencies are also found for the formation of dihydrogen vs. dihydride complexes and underline the analogy [Zn2Cp*2] ↔ H2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 30 publications
9
46
0
2
Order By: Relevance
“…The computed ZnFe length of 2.401 Å is identical to that found in [(py) 3 ZnFe(CO) 4 ] complex (2.4017(3) Å) and similar to other complexes containing this FeZn bond without bridging coligands . The calculated ZnNi distances (2.35‐2.43 Å range, Table ) match well with recent examples of complexes displaying this NiZn bond, reported by Fischer et al…”
Section: Resultssupporting
confidence: 86%
“…The computed ZnFe length of 2.401 Å is identical to that found in [(py) 3 ZnFe(CO) 4 ] complex (2.4017(3) Å) and similar to other complexes containing this FeZn bond without bridging coligands . The calculated ZnNi distances (2.35‐2.43 Å range, Table ) match well with recent examples of complexes displaying this NiZn bond, reported by Fischer et al…”
Section: Resultssupporting
confidence: 86%
“…[122] Based on crystallographic data and complementary computational studies, peripheral Zn···Zn interactions were found to be greatly affected by ancillary ligands and the electronic nature of the metal center,q uite similar to the formation of dihydrogen versus dihydride complexes.O wing to the significant ZnÀZn contraction observed for [Ni(ZnCp*)(ZnMe)(PMe 3 ) 3 ], the latter was denounced an organozinc congener of the Kubastype dihydrogen complex. [122] Based on crystallographic data and complementary computational studies, peripheral Zn···Zn interactions were found to be greatly affected by ancillary ligands and the electronic nature of the metal center,q uite similar to the formation of dihydrogen versus dihydride complexes.O wing to the significant ZnÀZn contraction observed for [Ni(ZnCp*)(ZnMe)(PMe 3 ) 3 ], the latter was denounced an organozinc congener of the Kubastype dihydrogen complex.…”
Section: E = Znmentioning
confidence: 99%
“…[Pd(ZnCp*) 4 -(CN t Bu) 2 ], and [Pd 3 Zn 6 (PCy 3 ) 2 (Cp*) 4 ]. [122] Based on crystallographic data and complementary computational studies, peripheral Zn···Zn interactions were found to be greatly affected by ancillary ligands and the electronic nature of the metal center,q uite similar to the formation of dihydrogen versus dihydride complexes.O wing to the significant ZnÀZn contraction observed for [Ni(ZnCp*)(ZnMe)(PMe 3 ) 3 ], the latter was denounced an organozinc congener of the Kubastype dihydrogen complex.…”
Section: E = Znmentioning
confidence: 99%
“…Die gesamte Bindungssituation kann jedoch auch als "side-on"-Koordination von Zn 2 Cp* 2 an das MCp*-Fragment verstanden werden. [122] Anhand der kristallographischen Daten und ergänzender Computerstudien wurden die peripheren Zn···Zn-Wechselwirkungen als stark abhängig von zusätzlichen Liganden und der elektronischen Natur des Metallzentrums erkannt, sehr ähnlich zur Bildung von Diwasserstoff-vs.D ihydridkomplexen. [122] Anhand der kristallographischen Daten und ergänzender Computerstudien wurden die peripheren Zn···Zn-Wechselwirkungen als stark abhängig von zusätzlichen Liganden und der elektronischen Natur des Metallzentrums erkannt, sehr ähnlich zur Bildung von Diwasserstoff-vs.D ihydridkomplexen.…”
Section: E = Znunclassified
“…Die gesamte Bindungssituation kann jedoch auch als "side-on"-Koordination von Zn 2 Cp* 2 an das MCp*-Fragment verstanden werden. Die daraus angedeutete Analogie zu "side-on"-koordinierten Diwasserstoff-Komplexen von Übergangsmetallen wurde füre ine Serie verwandter Organozink-Ni-und -Pd-Komplexe und -Cluster weiter untersucht, darunter [Ni(ZnCp*)(ZnMe)(PMe 3 ) 3 ], [Ni(ZnCp*) 2 (ZnMe) 2 (PMe 3 ) 2 ], [{Ni(CN t Bu) 2 (m 2 -ZnCp*)(m 2 -ZnMe)} 2 ], [Pd(ZnCp*) 4 (CN t Bu) 2 ]u nd [Pd 3 Zn 6 (PCy 3 ) 2 -(Cp*)4 ] [122]. Anhand der kristallographischen Daten und ergänzender Computerstudien wurden die peripheren Zn···Zn-Wechselwirkungen als stark abhängig von zusätzlichen Liganden und der elektronischen Natur des Metallzentrums erkannt, sehr ähnlich zur Bildung von Diwasserstoff-vs.D ihydridkomplexen.…”
unclassified